Desain Model Pembelajaran Integral Mata Kuliah Fiqh Ibadah Untuk Meningkatkan Kecerdasan Mahasiswa - Masykurillah, Masykurillah; Badaruddin, Muhammad (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2021)
This article describes the design of an integral learning model in the religious fiqh subject in order to improve students' spiritual intelligence. This study uses the R&D model; ADDIE steps 1-2 or level 1. This study is carried out in three stages, namely; draw up a theoretical basis for design; product design; and test the validity of the design. The validity test is carried out twice, each by four different validators and experts in their fields. Validation is also carried out on supporting devices in the form of religious fiqh teaching materials and learning outcome evaluation instruments. The data collection tools used were literature study and questionnaires. Based on the analysis that has been done, this research shows several things, namely: (1) several complementary theories are found so that it is feasible to design a learning model that can improve students' spiritual intelligence; (2) product creation in the form of an integral learning model design; (3) the validation test of the supporting theory and design obtained a score of 4.5 (very valid), the value of religious fiqh teaching materials was 4.8 (very valid), and the learning outcome evaluation instrument was 4.7 (very valid). Thus it can be stated that the design of this integral learning model is very feasible to be implemented in the religious fiqh course to improve students' spiritual intelligence.